2012
DOI: 10.1074/jbc.m112.393124
|View full text |Cite
|
Sign up to set email alerts
|

The Src Family Kinases and Protein Kinase C Synergize to Mediate Gq-dependent Platelet Activation

Abstract: Background:The role of SFKs in G protein-coupled receptor-mediated platelet activation is not well understood. Results: AYPGKF induced G q /Ca 2ϩ -dependent SFK phosphorylation, and AYPGKF-elicited platelet activation was partially inhibited by PP2 but was completely abolished by PKC inhibitors plus SFK inhibitors. Conclusion: Ca 2ϩ /SFKs/PI3K and PKC represent alternative pathways mediating AYPGKF-dependent platelet activation. Significance: This work increases understanding of important SFK functions in plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
3
24
0
1
Order By: Relevance
“…7 PAR-4-mediated SFK activation is inhibited by Ca 21 chelation, which supports the notion that SFKs are activated downstream of Ca 21 mobilization. 7 SFKs have been reported to lie upstream of PI3K 9 and work in conjunction with PKC to propagate PAR-4 signaling. 81 PAR-4-mediated platelet activation is only partially inhibited in the presence of a PKC inhibitor, Ca 21 chelator, or SFK inhibitor, but it is abolished by a PKC inhibitor in combination with either a Ca 21 chelator or SFK inhibitor.…”
Section: Sfks In Gpcr Signalingsupporting
confidence: 66%
See 2 more Smart Citations
“…7 PAR-4-mediated SFK activation is inhibited by Ca 21 chelation, which supports the notion that SFKs are activated downstream of Ca 21 mobilization. 7 SFKs have been reported to lie upstream of PI3K 9 and work in conjunction with PKC to propagate PAR-4 signaling. 81 PAR-4-mediated platelet activation is only partially inhibited in the presence of a PKC inhibitor, Ca 21 chelator, or SFK inhibitor, but it is abolished by a PKC inhibitor in combination with either a Ca 21 chelator or SFK inhibitor.…”
Section: Sfks In Gpcr Signalingsupporting
confidence: 66%
“…81 PAR-4-mediated platelet activation is only partially inhibited in the presence of a PKC inhibitor, Ca 21 chelator, or SFK inhibitor, but it is abolished by a PKC inhibitor in combination with either a Ca 21 chelator or SFK inhibitor. 6,7,81,82 Further evidence of the interplay between SFKs and PKC is that PKCd interacts directly with Fyn and is tyrosine phosphorylated at positions Tyr311 and Tyr565 in an SFK-dependent manner that potentiates PKC activity in response to thrombin. 81 This is consistent with the earlier finding that phosphorylation of Ser12 in the membranebinding domain of Src by PKC induces cytoskeletal association and an increase in substrate affinity.…”
Section: Sfks In Gpcr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing, precipitated proteins were analyzed by immunoblotting with the antiphosphotyrosine monoclonal antibody 4G10. 22 …”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…It was reported that platelet AKT signaling elicited by the binding of agonists to G-protein-coupled receptors is crucial for Ca 21 signaling 33 and that neutrophil AKT2 is critical for Ca 21 mobilization during cell activation. 1 To explain the differential regulation of Ca 21 signaling in platelets and neutrophils by NOX2, we examined the phosphorylation of AKT and MAP kinases ERK and p38.…”
Section: Platelet and Neutrophil Nox2 Differentially Modulate Ca 21 Mmentioning
confidence: 99%